PENILE NEOPLASM: AN ATYPICAL PRESENTATION - Sobia Rafi; Faizan Hussain; Rabia Shaikh; Anis Hussain (ziauddin University, 2019)
Penile carcinoma, representing less than one percent of all cancers in males, is a condition where diagnosis is frequently delayed, therefore the disease and its treatment results in significant morbidity and mortality in patients. There is no known etiology; however HPV infections are detected in most cases of penile cancer, so possible correlation may exist. Penile cancers usually present as an outgrowth or lesion on the penis with bleeding, itching or discharge. We are presenting an unusual case of a 43-year old circumcised male with penile cancer who had obstructive symptoms and diffuse thickening of penis without any external lesion or growth or known risk factors. The literature review revealed its rarity to best of our knowledge. Till date penile cancer continues to be a devastating disease, and its presentation is compounded by its psychological impact on the patient. Moreover, unusual thickening of penile shaft should be biopsied.